ADVANTAGES AND DISADVANTAGES OF DISTANCE EDUCATION - Nemchuk, Oleksii Olehovych; Strelbitskyi, Viktor Vasylovych (Distance Education in Ukraine: Innovative, Normative-Legal, Pedagogical Aspects, 2021)
The article analyzes the use of modern technologies, namely distance learning in higher education. The main advantages and disadvantages of distance education in modern conditions are considered.